2018
DOI: 10.1038/s41424-018-0060-1
|View full text |Cite|
|
Sign up to set email alerts
|

The Use of International Classification of Diseases Codes to Identify Patients with Pancreatitis: A Systematic Review and Meta-analysis of Diagnostic Accuracy Studies

Abstract: BackgroundHospital discharge codes are increasingly used in gastroenterology research, but their accuracy in the setting of acute pancreatitis (AP) and chronic pancreatitis (CP), one of the most frequent digestive diseases, has never been assessed systematically. The aim was to conduct a systematic literature review and determine accuracy of diagnostic codes for AP and CP, as well as the effect of covariates.MethodsThree databases (Pubmed, EMBASE and Scopus) were searched by two independent reviewers for relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…Numerous studies have been conducted on the accuracy of coding in other countries. The evaluation of the accuracy of diagnostic coding in the studies conducted by Xiao et al on chronic acute pancreatitis (10), Liu in patients with sarcoma (17), and Worfellan et al on patients with syncope (18) is not significantly different from the present study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Numerous studies have been conducted on the accuracy of coding in other countries. The evaluation of the accuracy of diagnostic coding in the studies conducted by Xiao et al on chronic acute pancreatitis (10), Liu in patients with sarcoma (17), and Worfellan et al on patients with syncope (18) is not significantly different from the present study.…”
Section: Discussioncontrasting
confidence: 79%
“…Numerous studies have been conducted on the quality and accuracy of coding which yielded contradictory results. Some of these findings pointed to poor coding quality, while some others demonstrated good results (8)(9)(10)(11)(12)(13)(14). In their study, Thomas et al1.…”
Section: Introductionmentioning
confidence: 89%
“…Of particular note, studies based on register data rather than individual case assessment may overestimate the incidence rate by 20-30% as the positive predictive value of a CP diagnosis using register data has been estimated to be 70-80%. 16,20 Prevalence estimates of CP have mostly been limited to studies based on non-population-based settings with relatively short observation periods. We observed the highest prevalence of CP reported to date in Europe (153.9 per 100,000 persons in 2016), which is considerably higher than prevalence estimates previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the use of ICD codes for pancreatitis might have overestimated its actual incidence in this study. A meta-analysis of 24 cohorts suggested that the overall diagnostic accuracy of ICD codes for pancreatitis is suboptimal, with the pooled estimate of positive predictive value of ICD codes for AP being 71% ( 36 ). However, the estimate improves to 78% when the study population is constrained to incident AP in adults, which was the case in this study.…”
Section: Discussionmentioning
confidence: 99%